Kristologi Kosmik Sebagai Upaya Konsolidasi Dalam Dialektika Antara Struktur Tana’bulaan Dan Tana’kuakua Di Toraja - Patandean, Wendi Triseptyadi; Ningrat, Rezky Brendina (Media: Jurnal Filsafat dan Teologi, 2024)
One of the characteristics of Toraja society is social stratification which is culturally legitimized. In social and cultural life there is a gap between Tana’ Bulaan (noble class) and Tana’ Bulaan (lower class). This article aims to find the roots of these social disparities and offers a theological solution based on Cosmic Christology as a consolidation effort. This research uses descriptive qualitative methods by collecting data through observation and interviews. Social inequality is often culturally legitimized through the mythology of the Creation Story. However, this social phenomenon also has its roots in economic factors. Understanding Cosmic Christology can be an inspiration for efforts to promote the harmony and togetherness of the two social strata. The essence of Jesus is as a powerful God and also as a human and a servant. Jesus, whose essence is God, does not intimidate or look down on humans, who are His essence.